The Odyssey - McCaughrean, Geraldine; Homer; Ambrus, Victor G. (New York : Puffin Books, 2015)
A retelling of Homer's epic that describes the wanderings of Odysseus after the fall of Troy.
5-8.
English.
Keywords: Mythology, Greek -- Juvenile literature; Mythology, Greek; Odysseus (Greek mythology) -- Fiction; Classical mythology